Pollution assessment and health risk of metals in surface soil near a Pb–Zn mine, northeast China - Wang, Hui; Yu, Siyi; Sun, Lina; Wang, Yinggang; Wu, Hao; Wang, Xiaoxu (Frontiers in Environmental Science, 2025)
The Chaihe Pb-Zn mine, one of the largest Pb-Zn mines in northeast China, began to be exploited aggressively in 1966, but the degree of environmental impact is not well understood. Therefore, this study conducts a systematic study on the farmland areas upstream, downstream and around the lead-zinc mine, and metals, such as chromium (Cr), nickel (Ni), mercury (Hg), zinc (Zn), cadmium (Cd), lead (Pb), copper (Cu), and arsenic (As), were detected. The coefficient of variation (CV) indicated that, with the exception of Cu, Ni, and Cr, the metals in the surface soil were markedly affected by human activities. Enrichment factors further demonstrated that Hg, Cd, Pb, and Zn primarily originated from anthropogenic sources, while As, Ni, and Cr mainly stemmed from natural sources. Geoaccumulation index (Igeo) values disclosed that the contamination of Cd and Hg in the areas was particularly severe. The USEPA health risk model was employed to calculate the non - carcinogenic risk (HI) and carcinogenic risk (CR). In terms of health risk, the order of mean HI is as follows: Pb > As > Hg > Cd > Cr > Zn > Cu > Ni, and the order of mean CR is As > Pb > Cr > Cd > Ni. The results also illustrated that oral ingestion was the most important during the three exposure pathways, and children were shown to be prone to metal pollution. The CR for children, adolescents, adults, and total lifetime were acceptable, but HI for children, and total lifetime were unacceptable. Therefore, the results indicated significant contamination of Pb, Zn, Cd, and Hg in the surface soil around the Pb–Zn mine, offering valuable insights for enhancing ecological restoration and environmental protection efforts.